Optimal tax policies with private-public clean-up, cross-border pollution and capital mobility - Hadjiyiannis, Costas,Hatzipanayotou, Panos,Michael, Michael S. (Univ., Center for Economic Studies [u.a.], 2002)
This paper builds a model of a region with two non-identical countries, cross-border pollution and free movements of goods and capital within the region. Pollution reduces welfare and there is simultaneous private and public pollution abatement. Public pollution abatement is financed with the use of lump-sum and pollution tax revenue. The introduction of public pollution abatement enables us to derive the optimal pollution taxes in terms of the marginal cost of public pollution abatement. We derive and compare for each country the Nash and cooperative lump-sum and pollution taxes and examine how cross-border pollution and capital mobility affect them. Finally, we examine the impact of capital mobility on the effectiveness of pollution taxes on net pollution.
Internetausg.: http://www.cesifo.de/pls/ifo_app/DocLinkCESifoDl?getDoc=cesifo_wp822.pdf
Keywords: Arbeitspapier; Graue Literatur; Umweltabgabe; Ökosteuer; Optimale Besteuerung; Grenzüberschreitende Umweltbelastung; Kapitalmobilität; Umweltschutz; Theorie